Analysis of Exosomal Biomarkers in Oral Fluids of Periodontal Patients - Sharfudeen, Mohammed Rathan (2025)
Exosomes, small extracellular vesicles enriched with markers such as CD63, play essential roles in cell communication and inflammatory regulation. In periodontal disease, salivary and gingival crevicular fluid (GCF) exosomes may act as carriers of inflammatory mediators like interleukin-1 beta (IL-1β), a key factor in periodontal tissue destruction. Evaluating these exosomal biomarkers may support non-invasive assessment of periodontal disease activity. A total of 20 subjects were enrolled and categorized into two groups: 10 periodontally healthy individuals and 10 with chronic periodontitis. Saliva and GCF samples were collected and processed for extracellular vesicle (EV) isolation using ultracentrifugation. The size distribution of exosomes was assessed using Dynamic Light Scattering (DLS). Western blotting was performed to detect the exosomal marker CD63, and IL-1β expression was quantified via RT-PCR. Correlation analyses between exosome sizes in saliva and GCF were conducted. Salivary exosome size was significantly larger in the periodontitis group (419.21±181.95 nm) than in the healthy controls (285.24±76.95 nm; p<0.001). GCF exosome size showed no significant difference between the groups. Salivary IL-1β expression, measured by 2^(–∆∆Ct), was significantly higher in the periodontitis group (5.22±2.42) compared to healthy controls (1.11±0.53; p=0.017). A strong positive correlation (r=0.967, p<0.001) was found between salivary and GCF exosome sizes in the periodontitis group. Western blot confirmed CD63-positive exosomes in all samples, with stronger bands observed in the disease group. Exosomalprofiling of saliva, particularly IL-1β expression and CD63 detection, presents a promising, non-invasive approach for diagnosing and monitoring periodontitis. These findings highlight the potential of salivary exosomes as surrogate indicators of periodontal inflammation and emphasize the need for further research to improve diagnostic accuracy. Results should be interpreted cautiously due to the pilot nature and small sample size.